2022
DOI: 10.1007/s11042-022-12653-1
|View full text |Cite
|
Sign up to set email alerts
|

IEFHAC: Image encryption framework based on hessenberg transform and chaotic theory for smart health

Abstract: Smart cities aim to improve the quality of life by utilizing technological advancements. One of the main areas of innovation includes the design, implementation, and management of data-intensive medical systems also known as big-data Smart Healthcare systems. Smart health systems need to be supported by highly efficient and resilient security frameworks. One of the important aspects that smart health systems need to provide, is timely access to high-resolution medical images, that form about 80% of the medical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…The reasonable choice of dynamic adjustment strategy is the main index of experience design. Ergonomic analysis, dynamic adjustment among sports equipment functions, sports equipment materials, safety, price, appearance, and other indicators can not only balance the relationship between global design and local design, but also improve the corresponding design ability [ 15 ]. From formula ( 8 ), we can see that in the initial design of sports equipment, we pay great attention to the global design ability, and in the later design, we pay attention to the local design, so different bees should dynamically choose the experience design according to the conditions.…”
Section: Related Conceptsmentioning
confidence: 99%
“…The reasonable choice of dynamic adjustment strategy is the main index of experience design. Ergonomic analysis, dynamic adjustment among sports equipment functions, sports equipment materials, safety, price, appearance, and other indicators can not only balance the relationship between global design and local design, but also improve the corresponding design ability [ 15 ]. From formula ( 8 ), we can see that in the initial design of sports equipment, we pay great attention to the global design ability, and in the later design, we pay attention to the local design, so different bees should dynamically choose the experience design according to the conditions.…”
Section: Related Conceptsmentioning
confidence: 99%
“…This can be achieved by increasing the key space. From the previous studies, it has been found that the algorithm is found to be more secure if it has a key space greater than 2 100 [17]. The key space can be analyzed based on the algorithm's sensitivity to the initial conditions.…”
Section: Key Space Analysismentioning
confidence: 99%
“…Their scheme performs comparably to state-of-the-art techniques. Based on Hessenberg's transform and chaotic theories, an encryption technique for smart health care systems has been suggested in (Jan et al, 2022). This scheme combines logistic map and sine map to generate the effect of confusion in the given data.…”
Section: Introductionmentioning
confidence: 99%